Resistensi Persekutuan Kaum Wanita (PW) Jemaat GKI Bait – Lahim Klasis Kokas dalam Memberdayakan Komuditas Primadona (Buah Pala) Masyarakat Lokal: Women's Association (PW) Resistance of the GKI Bait – Lahim Kokas Congregation in Empowering Primadona Commudities (Nuts) in Local Communities - Thonia Florence Ruhulessin, Cleopatriza (IGKOJEI: Jurnal Pengabdian Masyarakat, 2024)
ABSTRACT  The GKI Bait-Lahim Kokas congregation is in Fak-Fak Regency, Southwest Papua Province, Teluk Patipi District, Adora Village – Us. Fak-fak Regency is known as a district that grows a lot of nutmeg trees. In the cosmology of the Fak-Fak people, the nutmeg tree is believed to be like a mother who gives birth to life. The origin of the existence of nutmeg, in the local language called Henggi Thomantin in Fak-Fak, is through three birds, namely, the kum-kum bird, the taon-taon bird and the forest dove. These three birds eat nutmeg seeds from other places and carry the nutmeg seeds and then release them in several forests around the Fak-Fak area, then the nutmeg seeds grow in the Fak-Fak forest. Since the discovery of the nutmeg plant, they consider that the nutmeg plant is a gift that God has given them in their lives. Nutmeg can bear fruit and this nutmeg has high economic value starting from the fruit, seeds and flowers which can guarantee all their needs. Like nutmeg syrup which is made from nutmeg fruit, it is a traditional food with a high cultural taste, so nutmeg is considered to be able to give life to people from generation to generation. One of the retentions carried out to maintain the religious and economic cultural value of this local commodity is training in making nutmeg syrup for the women's fellowship at the GKI Bait-Lahim Kokas congregation. Keywords: Congregational economy; Henggi thomantin; Syrup   ABSTRAK Jemaat GKI Bait-Lahim Kokas berada di Kabupaten Fak-Fak, Provinsi Papua Barat Daya, Distrik Teluk Patipi, Kampung Adora – Us. Kabupaten Fak-Fak dikenal sebagai kabupaten yang banyak ditumbuhi pohon Pala. Dalam kosmologi orang Fak-Fak, pohon Pala dipercayai seperti ibu yang melahirkan kehidupan. Asal usul adanya Pala, dalam bahasa lokal disebut Henggi Thomantin di Fak-Fak, melalui tiga ekor burung diantaranya, burung kum-kum, burung taon-taon dan burung merpati hutan. Ketiga burung inilah yang memakan biji Pala dari tempat lain dan membawa biji Pala tersebut lalu melepaskannya di beberapa hutan sekitar daerah Fak-Fak kemudian biji-biji Pala itu tumbuh di hutan Fak-Fak. Sejak ditemukan tanaman pala ini maka masyarakat menganggap bahwa tanaman pala merupakan anugerah yang Tuhan berikan dalam kehidupan masyarakat. Pala bisa berbuah dan buah pala ini memiliki nilai ekonomi tinggi mulai dari buah, biji, dan bunga yang dapat menjamin segala kebutuhan masyarakat. Seperti sirup pala yang terbuat dari buah pala sebagai pangan tradisional yang bercita rasa budaya tinggi, Sehingga pala dinilai dapat memberi kehidupan kepada masyarakat secara turun-temurun. Salah satu resitensi yang dilakukan untuk mempertahankan nilai kultur religi dan ekonomi dari komuditas lokal ini adalah pelatihan pembuatan sirup pala kepada persekutuan wanita di jemaat GKI Bait-Lahim Kokas. Kata kunci: Ekonomi jemaat; Henggi thomantin; Sirup